Antioxidant and Sensorial Properties of Polyfloral Honey with Dried Apricots after One Year of Storage - Jelena Vulić; Jasna Čanadanović-Brunet; Gordana Ćetković; Sonja Djilas; Vesna Tumbas Šaponjac (Journal of Chemistry)
Total phenol (TPh) and flavonoid (TFd) contents, antioxidant and sensorial properties of polyfloral (PH), and polyfloral honey after one year of storage (PHs) with dried apricots (20, 30, and 40%) were evaluated. In comparison to honey, TPh increased 1.86 times for PH40. After storage time, TPh of PH40s increased slightly lower (1.77 times), compared to PHs. TFd slightly increased, approximately 3.23-fold, from PH to PH40, while PHs showed increase of 5.15-fold for PH40s. Antioxidant activity increased with increasing concentration of apricots in honey. EC50OH varied from 3.36 for PH to 2.29 mg/mL for PH40 and from 3.48 for PHs to 2.68 mg/mL for PH40s; EC50DPPH ranged from 30.60 for PH to 14.95 mg/mL for PH40 and from 31.22 for PHs to 17.43 mg/mL for PH40s; RP0.5 ranged from 66.37 for PH to 31.83 mg/mL for PH40 and from 67.99 for PHs to 35.03 mg/mL for PH40s. Statistical analysis suggested that TPh and TFd were associated with antioxidant activity and colour. Sensory parameters, before and after storage, indicated very good sensory qualities. Phenolic composition, antioxidant capacity, and sensory properties were promoted after addition of dried apricots and these parameters stayed improved, since antioxidant compounds present in dried apricots aided in maintenance of honey properties along one year of storage.